2010
DOI: 10.1016/j.socscimed.2010.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Social venues that protect against and promote HIV risk for young men in Dar es Salaam, Tanzania

Abstract: Developing effective place-based health interventions requires understanding of the dynamic between place and health. The therapeutic landscape framework explains how place-based social processes and physical geography interact and influence health behavior. This study applied this framework to examine how venues, or social gathering places, influenced HIV risk behavior among young, urban men in Tanzania. Eighty-three public venues where men ages 15-19 met new sexual partners were identified by community infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 37 publications
(61 reference statements)
3
81
0
Order By: Relevance
“…Participants in this study are male members of 59 “camps” within 4 wards of Dar es Salaam (Yamanis, Maman, Mbwambo, Earp, & Kajula, 2010). These camps were identified by the study team as groups occupying designated physical spaces where young men meet to socialize (Yamanis et al, 2010). Camps are stable social units; those included in the trial have been in existence for an average of eight years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study are male members of 59 “camps” within 4 wards of Dar es Salaam (Yamanis, Maman, Mbwambo, Earp, & Kajula, 2010). These camps were identified by the study team as groups occupying designated physical spaces where young men meet to socialize (Yamanis et al, 2010). Camps are stable social units; those included in the trial have been in existence for an average of eight years.…”
Section: Methodsmentioning
confidence: 99%
“…Camps are stable social units; those included in the trial have been in existence for an average of eight years. Men typically belong to only one camp and often pay membership fees to belong to that camp (Yamanis et al, 2010). Most camp members are not formally employed and spend several hours each day at their camp (Yamanis et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research identified stable social networks of mostly young men in Dar es Salaam, Tanzania who socialize regularly in what they call “camps” [23]. Camps consist of between 10 and 80 members and have elected leadership, membership fees, and a physical space to meet.…”
Section: Introductionmentioning
confidence: 99%
“…Camps are social gathering places where networks of mostly men frequent and have about 30-35 members and an average lifespan of 8 years [66]. They typically have elected leadership and some require membership fees to belong.…”
Section: Participant Recruitmentmentioning
confidence: 99%